Pemanfaatan Website WWW.Pulokambing.Com Sebagai Media Rumah Kreatif Bersatu Nusantara (RKBN) Pulokambing Dalam Pemberdayaan Masyarakat - Saktisyahputra Saktisyahputra (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
Along with the development of information technology which is now increasingly rapid, thus changing the way humans human ways of conveying information. At present various information has used internet media as a supporting medium between humans and other humans. Following these developments, Pulokambing Archipelago United Creative House (RKBN) also utilizes by changing the promotion system and conventional community empowerment system using a website as a promotional medium in empowering the community to disseminate information about the Non Governmental Organization (NG) which aims to promote its products and services. By carrying out the Public Relations strategy in managing the website, This NGO hopes that there will be progress in terms of promotion and community empowerment. The purpose of this study is to determine the utilization and strategies used by Public Relations to increase the number of website visitors. The object in this study is the website www.pulokambing.com with a research approach using (IMC) Integrated Marketing Communication Theory, Qualitative case study methods, constructivist paradigms, while for data collection techniques using interviews, observation and documentation.The results of the study indicate that the use of the www.pulokambing.com website as a promotional medium in introducing products and services online. And improve the image of the NGO. In addition, community empowerment programs at Pulokambing RKBN such as the Unified KSPSS Cooperative in Pulokambing relatives, Pulokambing kinship farmers (PKPK), Waste Bank Management and Pulokambing Education Tourism strengthen the Website www.pulokambing.com.